2013
DOI: 10.1016/j.biopsych.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Hypothesis of Accelerated Cerebral White Matter Aging in Schizophrenia and Major Depression

Abstract: Introduction Elevated rate of aging-related biological and functional decline, termed accelerated aging, is reported in patients with schizophrenia (SCZ) and major depressive disorder (MDD). We used diffusion tensor imaging (DTI) derived fractional anisotropy (FA) as biomarkers of aging-related decline in white matter (WM) integrity to test the hypotheses of accelerated aging in SCZ and MDD. Methods The SCZ cohort was composed of 58/60 SCZ patients/controls (age=20–60years). MDD cohort was composed of 136/35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 58 publications
(75 reference statements)
10
99
4
2
Order By: Relevance
“…One study found that those with schizophrenia exhibit accelerated decline of whole brain fractional anisotropy, an index of white matter integrity measured using diffusion-weighted MRI. 40 Other studies have reported that individuals with bipolar disorder exhibit accelerated grey matter reduction with age 41 and rapid decline of levels of brain-derived neurotrophic factor, an index of neuronal survival and integrity that is associated with aging effects in the brain. 42 Given that aberrant reward processing has also been reported in individuals with schizophrenia and bipolar disorder, [43][44][45][46] researchers might profitably take a transdiagnostic approach to identifying potential protective factors and treatment targets of accelerated cellular aging across psychiatric disorders.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 99%
“…One study found that those with schizophrenia exhibit accelerated decline of whole brain fractional anisotropy, an index of white matter integrity measured using diffusion-weighted MRI. 40 Other studies have reported that individuals with bipolar disorder exhibit accelerated grey matter reduction with age 41 and rapid decline of levels of brain-derived neurotrophic factor, an index of neuronal survival and integrity that is associated with aging effects in the brain. 42 Given that aberrant reward processing has also been reported in individuals with schizophrenia and bipolar disorder, [43][44][45][46] researchers might profitably take a transdiagnostic approach to identifying potential protective factors and treatment targets of accelerated cellular aging across psychiatric disorders.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 99%
“…This has led to a suggestion that schizophrenia is associated with accelerated biological aging (Anthes, 2014;Dawes et al, 2011;Kirkpatrick et al, 2008;Kochunov et al, 2013;Koutsouleris et al, 2014;Lindqvist et al, 2015;Okusaga, 2014;Schnack et al, 2016;Shivakumar et al, 2014). Whereas men have overall higher death rates than women, mortality ratios in schizophrenia (standardized to the general population with respect to age, race/ethnicity and geographic region) are higher in women than in men with schizophrenia, with cardiovascular disease being a leading cause of premature death in both genders (Olfson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez-Sánchez et al (2007) reported that when processing speed was removed from a multivariate model, the cognitive deficits observed in patients with schizophrenia were no longer significant compared with healthy controls. Furthermore, schizophrenia patients show an accelerated ageing decline in cerebral white matter linked to an accelerated decay in processing speed when compared to healthy participants in cross-sectional and longitudinal studies (Karbasforoushan et al, 2015;Kochunov et al, 2013;Liu et al, 2013;Ritchie et al, 2015). Thus, deficits in speed of information processing represent an important cognitive marker of risk (Gur et al, 2014;Seidman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%